Coatings for atmospheric corrosion: Effect of surface roughness and corrosion inhibitor additives at carbon steel - Scully, Leah (Curtin University, 2023)
Organic coatings provide long term protection from corrosive environments to our infrastructure and assets. However, they often fail to prior to their specified service lifetimes. This research shows the effect of surface preparation on the performance of organic coatings and defines efficiencies of corrosion inhibitors used as additives to assess compatibility with a model zinc-based organic coating. This study provides insights into improving coating applications that will allow for advancing corrosion mitigation strategies across industries.